2012
DOI: 10.4161/jig.23750
|View full text |Cite
|
Sign up to set email alerts
|

Successful endoscopic treatment of iatrogenic biloma as a complication of endosonography-guided hepaticogastrostomy: The first case report

Abstract: Endosonography (EUS)-guided biliary drainage is a novel therapeutic option for patients with biliary obstruction after failed endoscopic retrograde cholangiopancreatography (ERCP). Many case reports and series worldwide have shown satisfactory clinical outcomes in terms of technical and clinical success rates, which approach 80%-100%. However, these procedures need to be performed by experts to minimize the possible complications, which have been reported in as many as 14-35% of patients. The most common compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Our results might also have another advantage. Indications for EUS-BD have expanded not only for malignant tumors, but also for benign biliary diseases [19][20][21]. Compared with malignant biliary obstruction, the intrahepatic bile duct is less dilated in benign disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results might also have another advantage. Indications for EUS-BD have expanded not only for malignant tumors, but also for benign biliary diseases [19][20][21]. Compared with malignant biliary obstruction, the intrahepatic bile duct is less dilated in benign disease.…”
Section: Discussionmentioning
confidence: 99%
“…Among EUS-BD procedures, various interventional techniques via an EUS-guided hepaticogastrostomy (HGS) route have been described [15][16][17][18]. However, EUS-HGS shows disadvantages such as a risk of stent migration into the abdominal cavity or bile leakage if EUS-HGS fails [19,20]. Successful EUS-HGS is thus extremely important to prevent adverse events.…”
Section: Introductionmentioning
confidence: 99%
“…[17] Other adverse events such as liver abscess, biloma, and focal cholangitis are also concerned by blocking the branch of bile duct. [394041] Previously, Umeda et al . [42] reported the technical feasibility and safety of a newly designed 8F plastic stent dedicated for EUS-HES.…”
Section: An Optimal Stent For Eus-antegrade Interventionmentioning
confidence: 99%
“…The incidence of biliary peritonitis as an adverse event from a diagnostic FNA is low, though higher when EUS guided biliary drainage is used as a salvage therapy when ERCP fails. [104][105][106] There have been few anecdotal reports of malignant seeding of the needle track, that were lower than those associated with percutaneous sampling. [107][108][109] More recent studies have shown that preoperative EUS-FNA of pancreatic neoplasms was not associated with an increased risk of seeding or decreased overall survival.…”
Section: Adverse Events Associated With Endoscopic Ultrasound-fine Nementioning
confidence: 99%